2017
DOI: 10.1038/nmat5025
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin graphene-based membrane with precise molecular sieving and ultrafast solvent permeation

Abstract: Graphene oxide (GO) membranes continue to attract intense interest due to their unique molecular sieving properties combined with fast permeation rates 1-9 . However, the membranes' use has been limited mostly to aqueous solutions because GO membranes appear to be impermeable to organic solvents 1 , a phenomenon not fully understood yet. Here, we report efficient and fast filtration of organic solutions through GO laminates containing smooth two-dimensional (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
499
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(535 citation statements)
references
References 29 publications
26
499
9
1
Order By: Relevance
“…In recent years, in order to achieve SRNF membranes with high permeability and stability, many nanomaterials including graphene, Mxene, metal-organic frameworks (MOFs) have been applied to fabricate SRNF membranes [8]. Among these nanomaterials, MOFs often exhibit a poor chemical stability and more suitable for use in gas barrier applications [9][10][11][12][13] attentions due to their unique physicochemical properties, which has been proved in our experiments and elsewhere [14][15][16][17][18][19][20]. The unique two-dimensional (2D) structure and the good stability in organic solvents endow graphene nanomaterials to be an ideal candidate for creating novel membranes [15,[21][22][23].…”
Section: Introductionsupporting
confidence: 51%
“…In recent years, in order to achieve SRNF membranes with high permeability and stability, many nanomaterials including graphene, Mxene, metal-organic frameworks (MOFs) have been applied to fabricate SRNF membranes [8]. Among these nanomaterials, MOFs often exhibit a poor chemical stability and more suitable for use in gas barrier applications [9][10][11][12][13] attentions due to their unique physicochemical properties, which has been proved in our experiments and elsewhere [14][15][16][17][18][19][20]. The unique two-dimensional (2D) structure and the good stability in organic solvents endow graphene nanomaterials to be an ideal candidate for creating novel membranes [15,[21][22][23].…”
Section: Introductionsupporting
confidence: 51%
“…Several previously published studies suggested that permeation of membranes is controlled by the distance between graphene oxide layers provided by swelling and by the size of molecules in hydrated state. [63][64] Our experiments demonstrate that intercalation of sugars into GO structure occurs in not hydrated state. At least partial dehydration of molecules is required in order to explain observed inter-layer distance of ~9.5-10 Å in solution immersed BGO.…”
Section: Resultsmentioning
confidence: 65%
“…[32] Swelling in polar solvents is one of the most remarkable properties of graphite oxides and multilayered graphene oxide membranes/papers. [4,29,[34][35][36] Swelling is of key importance for almost all applications of GO, e.g. dispersion of GO in solutions, solution based chemical functionalization of GO, preparation of pillared porous GO materials, [32,[37][38][39] preparation of graphene oxide membranes and their permeation in filtration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…. As considerable progress has been achieved for GO laminates in water, the exploration of graphene-based laminates for OSN is of great significance due to the instability of polymeric membranes in an organic solvent, yet has been lacking because of the impermeability of organic solvent through sub-micrometer-thick GO membranes. Recently, Nair group optimized GO laminar structure and demonstrated the potential of ultrathin GO membranes for OSN by achieving >99.9% rejection of small organic dyes in methanol [11], thus opening up a new world of filtration and separation for graphene-based membranes.…”
Section: Graphene-based Membranes For Organic Solvent Nanofiltrationmentioning
confidence: 99%